Küreselleşme ve Yürütmenin Güçlendirilmesi: Siyasal Sistem Tartışmaları - (:unkn) unknown (My University, 2002)
0

After the 1980's, especially in 1990's national development politics have come to an end and a new stage started because of the globalisation of world economics and politics. International Monetary Found's 'stabilization programmes' and World Bank's 'structural adjustment programmes' are imposed especially on developing countries so that they need the reorganization of the constutitional instutitions in favor of the executive branch. in Turkey this process has begun with the '24 January' 1980 and discussions on to strengthen the executive branch. in this context presidential system or semi-presidential system is seen as a new model of government and guaranty of the stability of government. In crisis situations instead of asking which system is good. it is betler to strengthen the democratic participatory institutions, because the govermental system is determined by political culture and party system of the country.
Keywords: Uluslararası İlişkiler; Siyasi Bilimler